"Keep calm and earn more points": What research says about token economy systems. Issue 4 (2nd October 2022) - Smith, Jonathan; Guimond, Fanny-Alexandra; St-Amand, Jérôme; Olivier, Elizabeth; Chouinard, Roch
ABSTRACT: The use of reward systems is common in education, particularly at the primary school level. Indeed, there are very few classes in primary schools in which such systems are not implemented. Token economy are used to encourage students to adopt appropriate target social and academic behaviors. However, consensus on their effectiveness is lacking. It is beyond the scope of this article to determine whether token economy systems actually achieve their intended purpose. This article does provide important insights into their origins and offers an up-to-date overview of the research on their effects, which serve as a basis for recommendations to educators and administrators who may need to take a position on their use.